P59 Subanalyses of the Telaprevir lead-in arm in the realize study: response at week 4 is not a substitute for prior null response categorisation. (6th September 2011) - Foster, G
Abstract : Introduction: On treatment, a poor therapeutic response to peginterferon (P)/ribavirin (R) is defined as a <1 log10 decline in viral load at week 4. Null response (NR) to a current or prior course of PR is defined as a <2 log10 decline in HCV RNA at week 12. The FDA adopted the week 12 NR definition in its recent draft guidance. The REALIZE study uniquely enrolled classically defined prior NR, partial responders and relapsers, and included an arm with a PR lead-in (L-I) phase. This design allows a comparison of on treatment response after 4 weeks of PR with prior response categories, including a comparison of 'null response', as well as the relationship between < or −1 log10 RNA decline and SVR in response to T/PR treatment. Method: Patients in the lead-in arm (N=240) received 4 weeks of PR followed by telaprevir (T) 750 mg 8 hourly for 12 weeks combined with PR followed by 32 weeks of PR alone. Control patients (N=121) received 48 weeks of PR. All patients received pegylated interferon alfa-2a. Results: 10% of prior relapsers and 31–40% of partial responders (shaded cells), had <1 log10 decline in HCV RNA at week 4 in the control and L-I arm, respectively. SVR rates in the T L-I arm among prior relapsers and partial responders were higher (62% and 56%, respectively; combined SVR=58%) than in prior week 12 NR who experienced <1 log10 decline in HCV RNA (15%). Although patients with −1 log10 response at end of the L-I phase had the highest SVR rates, SVR in T/PR patients with <1 log10 was considerably higher (62±15%) than control (0%). Conclusion: Poor interferon responders on treatment (<1 log10 decline in HCV RNA at week 4) are not the same as prior PR NR (<2 log10 at week 12). SVR rates in T/PR patients were higher than control irrespective of their response (< or −1 log10) at the end of the L-I phase. Safety findings in the T arm were similar irrespective of week 4 response.